2022
DOI: 10.1177/02676591221117355
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and cost of post-cardiotomy extracorporeal support in the United States

Abstract: Background Extracorporeal membrane oxygenation (ECMO) has been used increasingly for cardiopulmonary rescue. Despite recent advances however, post-cardiotomy shock (PCS)-ECMO survival remains comparatively poor. We sought to evaluate outcomes and define factors that predict in-hospital mortality. Methods We used the Nationwide Inpatient Sample (NIS) to evaluate adult hospitalizations with a primary procedure code for coronary artery bypass grafting (CABG), and/or valve procedures performed between 2013 and 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Of six adult ECMO studies investigating mortality, five observed patients (83%) with higher SES measured by ZIP code median income or Medicare wage index had improved survival (88, 103, 122–124). Three showed no association with other outcomes (complications or readmissions) (56, 65, 125, 126). One study incorporating all ages (127) and four pediatric studies found no association between SES and outcomes (31, 77, 86, 107).…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Of six adult ECMO studies investigating mortality, five observed patients (83%) with higher SES measured by ZIP code median income or Medicare wage index had improved survival (88, 103, 122–124). Three showed no association with other outcomes (complications or readmissions) (56, 65, 125, 126). One study incorporating all ages (127) and four pediatric studies found no association between SES and outcomes (31, 77, 86, 107).…”
Section: Resultsmentioning
confidence: 91%
“…Eight studies reported improved survival in patients with private relative to government insurance (28, 77, 88, 89, 106, 123, 128, 129). Eight found no survival difference (55, 65, 81, 92, 130–133), with variable cost, complication, readmission, and LOS results (31, 33, 56, 70, 125, 126, 128, 134), including one with higher renal replacement in privately insured patients (83).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Post‐cardiotomy cardiogenic shock represents one of the most common ECLS indications in adults 2,3,4,5,14 . The current clinical scenario pushes every cardiac surgery unit to provide an ECLS service besides the normal cardiac surgery activity, regardless of the center's ECLS case load.…”
Section: Discussionmentioning
confidence: 99%
“…Post-cardiotomy cardiogenic shock represents one of the most common ECLS indications in adults. 2,3,4,5,14 The current clinical scenario pushes every cardiac surgery unit to provide an ECLS service besides the normal cardiac surgery activity, regardless of the center's ECLS case load. Nevertheless, to optimize outcomes, it is recommended that centers performing ECLS for cardiac failure achieve a minimum ECLS volume of 30 cases per year, with a substantial proportion being for cardiac failure.…”
Section: Discussionmentioning
confidence: 99%